A low-temperature method to produce highly reduced graphene oxide - Feng, Hongbin; Cheng, Rui; Zhao, Xin; Duan, Xiangfeng; Li, Jinghong (Nature communications, 2013)
Chemical reduction of graphene oxide can be used to produce large quantities of reduced graphene oxide for potential application in electronics, optoelectronics, composite materials and energy-storage devices. Here we report a highly efficient one-pot reduction of graphene oxide using a sodium-ammonia solution as the reducing agent. The solvated electrons in sodium-ammonia solution can effectively facilitate the de-oxygenation of graphene oxide and the restoration of π-conjugation to produce reduced graphene oxide samples with an oxygen content of 5.6 wt%. Electrical characterization of single reduced graphene oxide flakes demonstrates a high hole mobility of 123 cm 2 Vs −1 . In addition, we show that the pre-formed graphene oxide thin film can be directly reduced to form reduced graphene oxide film with a combined low sheet resistance (~350 Ω per square with ~80% transmittance). Our study demonstrates a new, low-temperature solution processing approach to high-quality graphene materials with lowest sheet resistance and highest carrier mobility. The chemical reduction of graphene oxide can provide large quantities of reduced graphene oxide for potential application in electronics and composite materials. Feng et al . report a highly efficient low-temperature one-pot reduction of graphene oxide that uses sodium-ammonia solution as the reducing agent.